Situation Report: Hungary, 3 March 1967 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Kadar Back from Moscow New Ambassador to Vienna Economic Cooperation with the West as One of the Aspirations of Hungarian Economic Policy Political and Social Perspectives and the New Economic Mechanism